Septic shock, hypercalcemia and hemophagocytic syndrome due to paracoccidioidomycosis in a 3-year-old girl - Rodríguez-Portilla, Ricardo (2021)
Objetive: Report the case of a girl who presented septic shock, hypercalcemia and hemophagocytic syndrome due to paracoccidioidomycosis. Case report: 3-year-old female patient with 2-month illness characterized by fever, lymphadenopathy, weight loss, abdominal distention, and severe anemia. She arrived in poor general condition, developed septic shock and a hemophagocytic syndrome. The hypercalcemia and dermal lesions were striking. A cervical ganglion biopsy and bone marrow aspirate were performed. In the latter, images compatible with Paracoccidioides were found, which were then confirmed with Grocott's stain. She was treated with amphotericin B and trimethoprim-sulfamethoxazole. The evolution was favorable and serum calcium came back to normal ranges. Conclusion: Complications caused by paracoccidioidomycosis are rare; however, the epidemiological history and bone marrow aspirate should guide the diagnosis and allow prompt treatment.